Review and Analysis of the Effectiveness of International Regulations and laws in the Field of Integrated Water Resources Management in Central Asia - Zh. E. Kulenbekov; S. Zh. Orunbaev; B. D. Asanov; E. P. Sakhvaeva (Проблемы постсоветского пространства)
An analysis of the effectiveness of the work of regulatory legal acts and laws of the Kyrgyz Republic on integrated water resources management was carried out in order to identify causal relationships of work / not work, as well as recommendations on the necessary measures for the effective work of regulatory legal acts (NLA) in this area were developed. Also, as part of the preparation of this work, successful cases were prepared on the work of the NLA and the laws of the Kyrgyz Republic and Central Asia, transboundary and basin water resources management. The work was structured as follows: collecting the necessary materials, studying, analyzing, making recommendations. To date, Kyrgyzstan has not implemented the provisions of the Water Code. The State Water Administration and its Basin Structures, Irrigation and Drainage Commissions, Dam Safety, etc. have not been created. Water resources management is still carried out on an administrative basis, not on a basin basis. The work used various literary sources, archival data, Internet resources, etc., links to which are given in the article.